2023
DOI: 10.3389/fphys.2023.1145129
|View full text |Cite
|
Sign up to set email alerts
|

Association of oxidative stress, programmed cell death, GSTM1 gene polymorphisms, smoking and the risk of lung carcinogenesis: A two-step Mendelian randomization study

Abstract: Aim: We aimed to examine the association of oxidative stress, programmed cell death, smoking, and the GSTM1 gene in the risk of lung carcinogenesis. The two-step Mendelian randomization will reveal evidence supporting the association of the exposure and mediators with the resulting outcome.Methods: In step 1, we estimated the impact of smoking exposure on lung carcinogenesis and programmed cell death. Our study involved a total of 500,000 patients of European ancestry, from whom we obtained genotype imputation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Although oxidative stress can promote the occurrence of tumors, long-term large amounts of ROS also have toxic effects on malignant tumors [15], and the effect of many anticancer methods depends on their ability to promote oxidative stress [16]. In addition, many studies have shown that oxidative stress is closely related to programmed cell death (such as autophagy, ferroptosis, cuproptosis), and oxidative stress can induce or activate programmed cell death [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Although oxidative stress can promote the occurrence of tumors, long-term large amounts of ROS also have toxic effects on malignant tumors [15], and the effect of many anticancer methods depends on their ability to promote oxidative stress [16]. In addition, many studies have shown that oxidative stress is closely related to programmed cell death (such as autophagy, ferroptosis, cuproptosis), and oxidative stress can induce or activate programmed cell death [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%